2023
DOI: 10.1007/s00432-023-04656-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gastrointestinal microbiome supplementation on immune checkpoint inhibitor immunotherapy: a systematic review

Abstract: Purpose Gastrointestinal (GI) microbiome modulators, such as fecal microbiome transplants (FMTs), are being considered as supplements to standard immune checkpoint inhibitor (ICI) treatment to improve efficacy. This systematic review aims to assess the study design and outcomes of clinical trials that use FMTs to enhance ICI treatment. Methods Systematic literature searches were conducted on PubMed and Embase using search terms that included names of ICIs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The main current IO approaches in ICI support outlined in Fig. 1 include a Mediterranean-style diet with over 20 g of fibre [12 ••, 50••], regular exercise [14], the use of live biotherapeutics [82][83][84], ensuring vitamin D repletion [13,97], and minimising PPI and antibiotic use [67,[74][75][76], with many other integrative oncology approaches under study. This area is ripe for further research, ranging from dietary intervention and dietary component studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main current IO approaches in ICI support outlined in Fig. 1 include a Mediterranean-style diet with over 20 g of fibre [12 ••, 50••], regular exercise [14], the use of live biotherapeutics [82][83][84], ensuring vitamin D repletion [13,97], and minimising PPI and antibiotic use [67,[74][75][76], with many other integrative oncology approaches under study. This area is ripe for further research, ranging from dietary intervention and dietary component studies, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A pan-tumour neoadjuvant window study of a LBT, MRx0518, demonstrated long-term safety and clear evidence of immune modulation with significant anticancer efficacy [ 82 ]. In another example, Clostridium butyricum MIYAIRI 588 strain (CBM588) has demonstrated significant improvement in ORR and median PFS as a combination therapy in patients receiving nivolumab-ipilimumab and may buffer detrimental impact of PPIs in NSCLC patients receiving ICI therapy [ 83 , 84 ]. LBTs have significant immune-modulatory effects through metabolites, such as short-chain fatty acids, enhancing response to ICIs clinically [ 85 , 86 ].…”
Section: The Gut Microbiome and Supplementation—live Biotherapeutics ...mentioning
confidence: 99%
“…Antibodies against the immunosuppressive molecule PD-1 and its ligand PD-L1, as well as CLTA4, have been used as ICIs to activate antitumor effects. Recently, some gut bacteria have been shown to enhance the efficacy of ICIs 97 …”
Section: Gut Microbiota and Antitumor Immunitymentioning
confidence: 99%